Simulation of cascading failures of power grids in Singapore - Tan, Junyuan. (2012)
As power relays are being controlled by computer networks, there is a possibility that a inside intruder may attack one of the node by causing it to trip, which then leads to other nodes in the network to trip, and this causes a cascading failure or a blackout to happen. Companies may not be able to function in the event of blackout and this may lead them to lose their daily revenue. In order to find out different ways of attacking the power grid network from the attacker’s point of view, a simulation of different ways of attacking was simulated on different networks. Simulations were simulated for different topologies, for symmetric, and Singapore’s 230kV network for transmission level simulation. It was observed that for lower loads, attacking lower loads is the best way of a best way of causing cascading failures of large extent under alpha<0.5. For greater alpha values, attacking higher loads, with SPC is the best way of causing cascading failure.